2016
DOI: 10.1177/0194599816655310
|View full text |Cite
|
Sign up to set email alerts
|

Stapedotomy vs Cochlear Implantation for Advanced Otosclerosis

Abstract: Cochlear implantation leads to a statistically greater and consistent improvement in speech recognition scores. Stapedotomy is not universally effective; however, it yields good results comparable to cochlear implantations in at least half of patients. For cases of unsuccessful stapedotomy, the option of cochlear implantation is still open, and the results obtained through salvage cochlear implantation are as good as those of primary cochlear implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 24 publications
2
27
2
1
Order By: Relevance
“…Unlike CI, stapes surgery does not require extrusive rehabilitation and avoids the need to change quality and tonality of sound. 10 As other studies have suggested, our findings show that some patients respond very well to stapes surgery, while for a minority, the results are unsatisfactory. In most cases, hearing thresholds are improved to a level where hearing aids are of benefit, and in 80% of patients, their thresholds improved to move them out of the category of ''profound'' hearing loss, so they would be no longer eligible for CI.…”
Section: Stapes Surgery Compared To CIsupporting
confidence: 76%
See 2 more Smart Citations
“…Unlike CI, stapes surgery does not require extrusive rehabilitation and avoids the need to change quality and tonality of sound. 10 As other studies have suggested, our findings show that some patients respond very well to stapes surgery, while for a minority, the results are unsatisfactory. In most cases, hearing thresholds are improved to a level where hearing aids are of benefit, and in 80% of patients, their thresholds improved to move them out of the category of ''profound'' hearing loss, so they would be no longer eligible for CI.…”
Section: Stapes Surgery Compared To CIsupporting
confidence: 76%
“…We also hope it will contribute to future meta-analyses, increasing the evidence available; the 2 published meta-analyses looking at this clinical question contain 4 and 9 articles, respectively. 10,22 These studies show that CI is more likely to improve hearing to a good standard overall, but that when stapes surgery is effective, it produces hearing that is nearly equivalent. 7,10,19,22 As yet, there is no complete consensus on the preoperative factors that can predict successful stapes surgery, although variables such as word recognition scores, benefit derived from hearing aid use, and extent of retrofenestral sclerosis have been suggested.…”
Section: Stapes Surgery Compared To CImentioning
confidence: 98%
See 1 more Smart Citation
“…As shown in several studies describing hearing improvement after stapedotomy in patients with severe to profound hearing loss, stapedotomy combined with hearing aids does not lead to many complications, and is relatively low cost, efficient and effective (post-operative disyllabic WRS at 60 dB = 50.6% for Kabbara et al) 9 . Moreover, stapes surgery does not preclude further cochlear implantation 4 9 10 .…”
Section: Introductionmentioning
confidence: 99%
“…2 After an extensive review of the literature, the authors identified 4 relevant papers that met their inclusion criteria. From their analysis, the authors concluded that cochlear implantation leads to significantly better speech recognition scores than stapedotomy; however, they noted significant variation in outcomes following stapedotomy.…”
mentioning
confidence: 99%